2022
DOI: 10.1161/strokeaha.121.034090
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Evidence for Stroke Family Caregiver and Dyad Interventions

Abstract: Stroke family caregiver and dyad literature has expanded over the past few years. The purpose of this review was to build upon 2 prior systematic reviews to critique, analyze, and synthesize the evidence pertaining to the impact of family caregiver and dyad interventions on stroke survivor and family caregiver outcomes. CINAHL, PsychINFO, PubMed, and reference lists were searched from December 1, 2016 through March 31, 2021. Using PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Although additional research is warranted, our study contributes to advancing the science of stroke caregiving. Our study includes all the recommendations of three reviews 20,21,50 for designing and implementing stroke caregiver interventions. Our intervention combined active skill-building with psychoeducational strategies, was individualized to the needs of the stroke caregivers, consisted of the recommended five to nine sessions, and included post-discharge assessments and instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Although additional research is warranted, our study contributes to advancing the science of stroke caregiving. Our study includes all the recommendations of three reviews 20,21,50 for designing and implementing stroke caregiver interventions. Our intervention combined active skill-building with psychoeducational strategies, was individualized to the needs of the stroke caregivers, consisted of the recommended five to nine sessions, and included post-discharge assessments and instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Educational and skills-based interventions have aimed at improving caregiver knowledge and perceived competence by providing information on stroke events, practical skills for caregiving, and general coping skills (e.g., emotion regulation) [ 37 ]. These interventions, which are often delivered by nurses, social workers, or psychologists, have demonstrated beneficial effects on stroke caregivers’ mental health [ 37 , 38 , 39 , 40 , 41 ]. While caregivers in the current review reported a desire to “know” (e.g., about the stroke event, caregiving skills, and survivor prognoses), they also identified concerns about the accessibility of information provided to them by hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Dyadic interventions are typically delivered by a trained provider either in-person or via telehealth and commonly range from 6 to 16 sessions (Backhaus et al, 2019; Martire et al, 2010; Vranceanu et al, 2020). A growing body of literature supports the feasibility and clinical benefits of dyadic psychosocial interventions with rehabilitation populations, including TBI (Kreutzer et al, 2020) and stroke (Bakas et al, 2022 ), as well as in the context of serious and/or chronic illnesses, such as cancer (Traa et al, 2015), heart failure (Buck et al, 2018), and dementia (Moon & Adams, 2013). However, dyadic psychosocial interventions have yet to be studied among the heterogeneous group of older patient–care-partner dyads in postacute rehabilitation settings.…”
Section: Postacute Rehabilitation and Psychosocial Dyadic Distressmentioning
confidence: 99%